Developmental Differences in Endogenous Control & Attentional Capture - Hayre, R.K. (2021)
Aims: The ability to plan-ahead allows us to focus our attention at an early stage of processing and is said to facilitate our ability to ignore distractions. This thesis aimed to track the development of endogenous control across the lifespan and assess if this skill can prevent attentional capture from a salient distraction. I used the Cued Visual Search task to understand whether children and adults can maintain early cues to guide their attention towards a target and suppress a salient distracter.